Peningkatan Kapasitas Aparatur Pemerintah Desa Melalui Pemberdayaan Masyarakat di Kecamatan Sabbangparu Kabupaten Wajo - Nawawi, Juanda; Anwar, Sakaria To; Kasogi, Adnan; Muhajir, Ahmad; Ilyas, Sadriani; Arisnawawi, Arisnawawi; Saifuddin, Saifuddin (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
Many cases show that village government officials have very limited capacity in empowering their communities. This is influenced by the low level of education and limited experience. Such village officials cannot carry out various innovative steps to advance their village. This situation is the background for the implementation of governance that is not perfectly implemented at the village level which results in hampered development in the region. In general, the capacity of the village apparatus in Sabbangparu District is also not maximized in supporting the community empowerment process. So it is very important to increase the capacity of the village apparatus in empowering the people in their village. The activity was carried out by providing outreach to increase the capacity of the village apparatus in empowering the community. Socialization material is presented interactively by stimulating the participants' minds so they can express their opinions and problems. This activity provides understanding to village apparatus to know their field of work well, especially their roles and functions. In addition, village officials also gain a comprehensive understanding of community development and empowerment, so they can formulate programs and mobilize communities in village development activities. Village apparatus received guidance in recognizing their respective potentials. This activity is not seen as just a transfer of knowledge but is far more important for elevating human dignity in the countryside.